1993
DOI: 10.1128/jb.175.5.1484-1492.1993
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and functional analysis of the multiple antibiotic resistance (mar) locus in Escherichia coli

Abstract: A 7.8-kbp fragment of chromosomal DNA from a region controlling multiple antibiotic resistance (Mar) in Escherichia coli has been sequenced. Within the fragment is a potential divergent promoter region including marO, which contains two pairs of direct repeats, suggesting possible operator-regulatory sites. To the left of marO (region I) are one or two transcriptional units with three putative open reading frames (ORFs) encoding 64, 157, and 70 amino acids. To the right (region II) is a transcriptional unit co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
450
1
2

Year Published

1995
1995
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(465 citation statements)
references
References 29 publications
12
450
1
2
Order By: Relevance
“…Such a pleiotropic mutation in a regulatory gene causing multi-drug resistance has been reported in mar mutants of E. coli (Cohen et al 1989(Cohen et al , 1993. In these mutants, both reduction of the outer membrane permeability and suppression of OmpF synthesis were observed, as in strain OW66 described in this study.…”
Section: Discussionsupporting
confidence: 71%
“…Such a pleiotropic mutation in a regulatory gene causing multi-drug resistance has been reported in mar mutants of E. coli (Cohen et al 1989(Cohen et al , 1993. In these mutants, both reduction of the outer membrane permeability and suppression of OmpF synthesis were observed, as in strain OW66 described in this study.…”
Section: Discussionsupporting
confidence: 71%
“…SoxS is a member of the AraC subfamily of helix-turn-helix proteins (1,13,41). Within this subfamily, the proteins encoded by soxS (1,41), tetD (4,31), marA (6,7), and rob (37) are highly homologous to one another over the entire 107-amino-acid length of SoxS, with the extent of homology ranging from 42% identity for the SoxS-MarA pair to 59% identity for the TetD-Rob pair. Even more striking is the fact that among the four proteins, at least three have the identical amino acid at 17 of the 21 positions of the respective helix-turn-helix motifs and at 10 of the 11 positions of the turn and the second, recognition helix.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, E. coli strains deleted for zwf are hypersensitive to oxidative stress, thus making zwf a pivotal member of the soxRS regulon (18, 21). In addition, treatment of cells with several antibiotics and aromatic weak acids appears to activate zwf transcription through the action of marA, thus making zwf a member of the multiple antibiotic resistance (mar) regulon (2,6,7,14,16).…”
mentioning
confidence: 99%
“…5). PecS (Reverchon et al, 1994), Hpr (Perego & Hoch, 1988), HpcR (Roper et al, 1993), EmrR (del Castillo et al, 1991) and MarR (Cohen et al, 1993) have all been shown to be negative regulators of bacterial gene expression. The B. fibrisoluens sequence is most similar to HpcR, a negative regulator of the homoprotocatechuate degradative operon of E. coli C (Roper et al, 1993), and PecS, a negative regulator of pectinase, cellulase and blue pigment production in Erwinia chrysantherni (Reverchon et al, 1994), with 31 Yo and 26 '/o amino acid identity respectively.…”
Section: High-level Expression Of Cinb In E Colimentioning
confidence: 99%